If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -6) * 10 = 70 Reorder the terms: (-6 + n) * 10 = 70 Reorder the terms for easier multiplication: 10(-6 + n) = 70 (-6 * 10 + n * 10) = 70 (-60 + 10n) = 70 Solving -60 + 10n = 70 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 10n = 70 + 60 Combine like terms: -60 + 60 = 0 0 + 10n = 70 + 60 10n = 70 + 60 Combine like terms: 70 + 60 = 130 10n = 130 Divide each side by '10'. n = 13 Simplifying n = 13
| 65=-4(5b+3) | | 108-3x=4x+17 | | 14-6x=6-8x | | 7(2y-3)=28 | | 8x^3+4x^2-34x+15=0 | | -3(4-2w)=10 | | 3(4-3s)=34 | | 3g+15=5g-3 | | 9x+23=3x+197 | | -3(4-2n)=19 | | -3(4-2)=19 | | 2x+3=2(2x+7) | | 5x+26=15x-64 | | x*x=x | | x+2x-3x+4x-5x=-5 | | 2x^2-4kx+k=0 | | 9x^4-3x^2+1= | | 3x*2+5x+3=0 | | 2(x+1)-(x+2)=3 | | 2(x+1)-(x-2)=3 | | 72-3x=6x+24 | | 25xsomthing=105 | | 0.25(2-x)=9 | | 3(2x+5)=29-x | | 21=0.3(3-4x) | | 21=0.3(3-4) | | 21=0.393-40 | | 65=5(4-3x) | | 4x^2-8x-5=-5 | | 0.5(4-2x)=24 | | 5(3+2x)=25 | | 2x^2+2x+9=0 |